2016
DOI: 10.1186/s40064-016-2170-0
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method for tracking a magnetic target using scalar magnetometer array

Abstract: The position of a magnetic target can be obtained through magnetic anomaly which is measured by a magnetic sensor. Comparing with vector magnetic sensor, the measurement value of the scalar magnetic sensor is almost not influenced by its orientation in measurement coordinate axes. Therefore, scalar magnetic sensors can be easily assembled into an array. Based on analysis of the total scalar magnetic anomaly measured by scalar magnetometer, we present an efficient method for tracking a magnetic target using sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Ren et al [28] demonstrated a data acquisition system for magnetic localization and orientation with an error of only 2.1 mm, but required 80 sensors aligned in four planes to achieve this. This is similar to other works that implement a large number of magnetic sensors or sensing coils, [19,[22][23][24][25][26] which increases the complexity and reduces the likelihood of large-scale adoption, in practice. Mashraei et al [29] manufactured a flexible tunnel magnetoresistance sensor that attaches to the tip of a catheter and allows the determination of the catheter orientation using the geomagnetic field.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…Ren et al [28] demonstrated a data acquisition system for magnetic localization and orientation with an error of only 2.1 mm, but required 80 sensors aligned in four planes to achieve this. This is similar to other works that implement a large number of magnetic sensors or sensing coils, [19,[22][23][24][25][26] which increases the complexity and reduces the likelihood of large-scale adoption, in practice. Mashraei et al [29] manufactured a flexible tunnel magnetoresistance sensor that attaches to the tip of a catheter and allows the determination of the catheter orientation using the geomagnetic field.…”
Section: Introductionsupporting
confidence: 77%
“…[ 28 ] demonstrated a data acquisition system for magnetic localization and orientation with an error of only 2.1 mm, but required 80 sensors aligned in four planes to achieve this. This is similar to other works that implement a large number of magnetic sensors or sensing coils, [ 19,22–26 ] which increases the complexity and reduces the likelihood of large‐scale adoption, in practice. Mashraei et al.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Nelson and McDonald (2001) designed a multi-sensor towed array to detect the buried unexploded ordnance. Fan et al (2016aFan et al ( , 2016b proposed the method to locate a magnetic target based on a scalar sensor array. In this study, we focused on the tracking of the moving target by using total field magnetometers.…”
Section: Introductionmentioning
confidence: 99%